2017
DOI: 10.1111/ggi.13047
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is a risk factor for falling in independently living Japanese older adults: A 2‐year prospective cohort study of the GAINA study

Abstract: The key finding of the present study suggests that sarcopenia is a risk factor for falling in older adults who are living independently even after adjustment for previous falls and confounding factors. Geriatr Gerontol Int 2017; 17: 2124-2130.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls . Most of the studies were performed in Europe (12 studies), and Asia (12 studies), followed by Australia (5 studies), South America (4 studies), and North America (3 studies) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls . Most of the studies were performed in Europe (12 studies), and Asia (12 studies), followed by Australia (5 studies), South America (4 studies), and North America (3 studies) .…”
Section: Resultsmentioning
confidence: 99%
“…Online Resource S4 shows the results of the NOS quality assessment of the included studies. The quality of 12 falls studies and 14 fracture studies was rated high. Ten studies for falls were rated as low quality .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations